Diversity and homogeniety in cyberspace : a study of website content preferences of selected ethno-linguistic groups - Martinez Santa Cruz, Adriana (My University, 2007)
The Internet has revolutionized the ways we communicate and interact with each other. An intriguing question that has baffled both technologists and social scientists is, "Does the Internet empower different ethno-linguistic groups to assert their cultural diversity more effectively or does it exert an homogenizing influence that diminishes ethno-cultural uniqueness?" During the past few years the researchers have been tracking the rise and falls of the top ranking Internet sites. In this project, we examine the contents distribution (or major functional purposes) of these most frequently visited Websites (called the Top 100 Websites) of different language groups. It was found that there were considerable differences in content preference among the different language groups, lending credence to the assumption of a strong heterogenizing influence in Internet-mediated communication.
Do different ethno-linguistic groups exhibit different content preferences among the top-ranking internet web sites?
Color poster with text, graphs and charts describing research conducted by Adriana Martinez Santa Cruz advised by Bruce W. N. Lo.
Keywords: Internet--Research; Web sites--Design; Web sites--Evaluation; Communication and technology; Information technology--Social aspects; Communication--Social aspects; Language and culture; Anthropological linguistics; Posters